Contact time in GP Care: Descriptive patterns and a scoping review of the literature - Reif, Simon; Köhler, Jan; Schubert, Sabrina; Stelter, Benedikt (Health policy (Amsterdam, Netherlands), 2025)
Background: Contact time in general practice (GP) refers to the duration a physician spends with a patient during an appointment. There are significant differences in contact times across OECD countries, raising questions about the influencing factors and potential consequences of these variations. Objective: To study the determinants and consequences of the length of consultations in GP care. Method: We descriptively investigate differences in average appointment durations in GP care across OECD countries. We then conduct a scoping review of the literature encompassing 150 studies in seven topical clusters. Results: We identify considerable differences in contact times across countries and find evidence for substitution effects between the length of consultations and the number of consultations per year. There is also an association between reimbursement schemes and visit lengths. The review reveals consistent evidence for a few determinants, such as patient characteristics and physician experience, but mixed evidence on the effects of contact time on shared decision-making and health outcomes. The literature is dominated by correlational studies. Conclusion: Descriptive comparisons show shorter contact times are substituted with more frequent visits, and fee-for-service payment systems result in longer contact times compared to capitation systems. For future health policy discussions, it is crucial to clarify which service delivery form is socially desired and economically sustainable.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Contact time; GP care; Health policy; Literature review